2021
DOI: 10.4102/sajce.v11i1.854
|View full text |Cite
|
Sign up to set email alerts
|

The impact of different approaches to the teaching of Grade 5 fraction by three experienced teachers

Abstract: Background: Many teachers for different reasons recognise the teaching of fraction as a challenge. This research explored the teaching of fraction in Grade 5 by three experienced teachers (Ben, Greg and Will) in KwaZulu-Natal province, South Africa.Aim: The purpose of this study was to investigate the impact of different approaches to the teaching of Grade 5 fraction by three experienced teachers.Method: Three teachers and 177 learners were purposively sampled for this study. Classroom observations, interview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(45 reference statements)
1
2
0
1
Order By: Relevance
“…The educator's response suggested that Mathematics educators must know the content and successfully use various communication in the classroom. This aligns with the sentiments shared by Stols et al (2015) and Ubah (2021) that Mathematics educators should use PBL in the classroom because it emphasises student-centeredness with learning activities that complement the various learning demands and their diverse home backgrounds.…”
Section: Resultssupporting
confidence: 71%
“…The educator's response suggested that Mathematics educators must know the content and successfully use various communication in the classroom. This aligns with the sentiments shared by Stols et al (2015) and Ubah (2021) that Mathematics educators should use PBL in the classroom because it emphasises student-centeredness with learning activities that complement the various learning demands and their diverse home backgrounds.…”
Section: Resultssupporting
confidence: 71%
“…When considering research on mathematics teaching in Southern Africa, it is noticed that several studies investigate the effectiveness of different kinds of interventions, approaches or resources. For instance, Ubah (2021) explored different approaches to the teaching of fractions in Grade 5. This study was conducted in the KwaZulu-Natal province of South Africa and involved three experienced Mathematics teachers and their learners.…”
Section: Recent Research In Southern Africamentioning
confidence: 99%
“…2017). Seyogyanya materi awal pecahan diajarkan menggunakan pendekatan yang dekat dengan kehidupan siswa (Ifunanya, 2021). Hal ini mendorong pembelajaran menjadi bermakna bagi siswa karena materi yang disajikan tersebut bisa dibayangkan dalam pikiran siswa (Punzalan, 2018).…”
Section: Pendahuluanunclassified